Validation and calibration of HeadCount, a self-report measure for quantifying heading exposure in soccer players - Catenaccio, E.; Caccese, J.; Wakschlag, N.; Fleysher, R.; Kim, N.; Kim, M.; Buckley, T. A.; Stewart, W. F.; Lipton, R. B.; Kaminski, T.; Lipton, M. L. (Research in Sports Medicine, 2016)
The long-term effects of repetitive head impacts due to heading are an area of increasing concern, and exposure must be accurately measured; however, the validity of self-report of cumulative soccer heading is not known. In order to validate HeadCount, a 2-week recall questionnaire, the number of player-reported headers was compared to the number of headers observed by trained raters for a men`s and a women`s collegiate soccer teams during an entire season of competitive play using Spearman`s correlations and intraclass correlation coefficients (ICCs), and calibrated using a generalized estimating equation. The average Spearman`s rho was 0.85 for men and 0.79 for women. The average ICC was 0.75 in men and 0.38 in women. The calibration analysis demonstrated that men tend to report heading accurately while women tend to overestimate. HeadCount is a valid instrument for tracking heading behaviour, but may have to be calibrated in women.